2022
DOI: 10.3389/fcimb.2022.964283
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and human health risk assessment of antibiotics in cultured fish from 19 provinces in China

Abstract: The occurrence of antibiotics and potential health risk of 300 cultured fish samples from 19 provinces in China were investigated. The levels of 28 antibiotics (15 fluoroquinolones, 4 tetracyclines, 8 macrolides and rifampin) in 8 fish species were measured through liquid chromatography electrospray tandem mass spectrometry. As a result, 10 antibiotics were detected with an overall detection frequency of 24.3%, and the individual detection frequency of antibiotics ranged from 0.33 to 16.7%. The extremely high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 66 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…The use of antibiotics in aquaculture is primarily for disease prevention and treatment, but overuse and misuse can lead to the development of antibiotic-resistant bacteria in aquatic environments [23], posing serious implications for human health. QNs, especially enrofloxacin and its metabolite ciprofloxacin are usually detected in marine fish, as reported by previous studies [24][25][26][27]. However, our study revealed that antibiotics with high detection frequency were CAPs and TCs in gastropod samples, unlike fish.…”
Section: The Distribution Of Antibiotics Illegal Drugs and Toxic Elem...supporting
confidence: 73%
“…The use of antibiotics in aquaculture is primarily for disease prevention and treatment, but overuse and misuse can lead to the development of antibiotic-resistant bacteria in aquatic environments [23], posing serious implications for human health. QNs, especially enrofloxacin and its metabolite ciprofloxacin are usually detected in marine fish, as reported by previous studies [24][25][26][27]. However, our study revealed that antibiotics with high detection frequency were CAPs and TCs in gastropod samples, unlike fish.…”
Section: The Distribution Of Antibiotics Illegal Drugs and Toxic Elem...supporting
confidence: 73%
“…Additionally, in some cases, the reason for high levels of tetracycline antibiotics in fish samples could be the use of substances containing antibiotics, like poultry manure, to improve plankton growth in aquaculture systems [ 43 ]. The maximum residual limits (MRL) of 100 μg/kg established by the European Commission [ 14 ] were not exceeded in any of the present study's tilapia samples that were contaminated with TCs.…”
Section: Resultsmentioning
confidence: 71%
“…This inevitably exposes aquatic organisms, starting with algae as the primary consumers in the food chain, to the ecotoxic effects of these residual antibiotic residues [ 12 ]. Earlier studies reported the occurrence of antibiotics in cultured fish from China [ [13] , [14] , [15] ], Argentina [ 16 ], Iran [ 17 ], and South Korea [ 18 ]. These studies reported various antibiotics in varying concentrations from different classes, such as tetracyclines, sulphonamides, quinolones, potentiators, pleuromutilin, penicillin, macrolides, lincosamides, cephalosporins, and amphenicols.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, humans and animals could be exposed to different compounds that can be simultaneously present in the environment; so, low concentrations should also be considered when referring to the cumulative risk. Moreover, long-term exposure to antibiotics trace levels can also lead to AMR and important changes in gut microbiota [70].…”
Section: Application To Real Samplesmentioning
confidence: 99%